Stump Appendicitis with Diagnostic Dilemma: A Case Report - Sah, Anil Kumar; Pandit, Rajeev Kumar; Shrestha, Muza; Maharjan, Sundar; Sah, Suman Prasad (Journal of Gandaki Medical College-Nepal, 2022)
Stump appendicitis is a rare delayed complication of incomplete appendectomy. The clinical symptoms and signs are like acute appendicitis. The possibility of stump appendicitis is not clear to all clinicians. It represents a diagnostic dilemma with incidence of one in 50,000 cases. We report how we encountered diagnostic dilemma during the management of a 30 years old male patient of acute abdomen with history of appendectomy done for acute appendicitis even years back.